Inhibition of transforming growth factor-activated kinase 1 (TAK1) blocks and reverses epithelial to mesenchymal transition of mesothelial cells. - Raffaele Strippoli (Public Library of Science (PLoS), 2012)
Peritoneal fibrosis is a frequent complication of peritoneal dialysis following repeated low grade inflammatory and pro-fibrotic insults. This pathological process may lead to ultrafiltration failure and eventually to the discontinuing of the therapy. Fibrosis is linked to epithelial to mesenchymal transition (EMT) of the peritoneal mesothelial cells, which acquire invasive and fibrogenic abilities. Here, we analyzed the role of the transforming growth factor-activated kinase-1 (TAK1) in the EMT of primary mesothelial cells from human peritoneum. The inhibition of TAK1 in mesenchymal-like mesothelial cells from the effluents of patients undergoing peritoneal dialysis led to the reacquisition of the apical to basolateral polarity, to increased expression of epithelial and to down-regulation of mesenchymal markers. TAK1 inhibition also resulted in decreased migratory/invasive abilities of effluent-derived mesothelial cells. Simultaneous inhibition of ERK1/2 and TAK1 pathways did not lead to an additive effect in the reacquisition of the epithelial phenotype. Inhibition of TAK1 also blocked EMT in vitro and reduced the levels of PAI-1, which is involved in fibrosis and invasion. Analysis of signalling pathways downstream of TAK1 involved in EMT induction, showed that TAK1 inhibition reduced the transcriptional activity of NF-κB and Smad3, as well as the phosphorylation of c-jun, while enhancing Smad1-5-8 activity. These results demonstrate that TAK1 is a cross-point in a network including different pro-EMT transcription factors, such as NF-κB, Snail, AP-1 and Smads. The identification of TAK1 as a main biochemical mediator of EMT and fibrosis in mesothelial cells from human peritoneum and the study of signalling pathways induced by its activity may be relevant in the design of new therapies aimed to counteract peritoneal fibrosis.